2010
DOI: 10.4085/1062-6050-45.4.386
|View full text |Cite
|
Sign up to set email alerts
|

National Collegiate Athletic Association Division I Football Players' Perceptions of Women in the Athletic Training Room Using a Role Congruity Framework

Abstract: Both quantitative and qualitative evidence were provided for the support of role congruity theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 12 publications
(19 reference statements)
2
16
0
Order By: Relevance
“…Another qualitative theme from our results revealed concepts that were similar to those from previous research 13 regarding Division I football players' perceptions of female ATs in the athletic training clinic. Both studies showed that student-athletes recognized ATs had the same level of education and background and, in general, did not have a preference on ATs for the majority of injuries.…”
Section: Selection Of Health Care Providerssupporting
confidence: 82%
See 2 more Smart Citations
“…Another qualitative theme from our results revealed concepts that were similar to those from previous research 13 regarding Division I football players' perceptions of female ATs in the athletic training clinic. Both studies showed that student-athletes recognized ATs had the same level of education and background and, in general, did not have a preference on ATs for the majority of injuries.…”
Section: Selection Of Health Care Providerssupporting
confidence: 82%
“…7 However, despite this move toward inclusivity, bias and discrimination (particularly gender discrimination) exist in athletic training. 12,13 Female ATs have experienced discrimination simply based on hir (gender-neutral pronoun, equivalent to his or her) gender. 12 Specifically, male football players were more comfortable with male ATs for treating both general medical conditions and sexspecific injuries and conditions, 13 although the athletes recognized that all ATs were required to take the same certification examination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,9,11 To deepen the information collected and truly capture the phenomenon of interest, we asked an expert on gender concerns in sport to review the content and structure of the interview guide (Appendix). This process allowed us to verify the content of the interview guide and the interpretability of the questions.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence suggests that some female ATs had their knowledge questioned, 9 were stereotyped as ''nurturing, soft, and a team mom,'' 10 and were perceived to be better at taking care of a family than participating in the workplace. 2 Additionally, despite football players' believing that female ATs possessed the necessary skills, 11 female ATs may be viewed more as sexual objects than as professionals. 12 Even with the challenges involved in gaining access to providing medical care to male sport teams, opportunities for women appear to be growing.…”
mentioning
confidence: 99%